2023
DOI: 10.1111/cobi.14050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IUCN Red List category on public attention to mammals

Abstract: Cultural data is a powerful tool to analyze public awareness of key societal issues, including the conservation of nature. I used two publicly available repositories of cultural data, Google Trends and Google Ngram, to quantify the effect of the International Union for the Conservation of Nature (IUCN) Red List conservation status on public attention toward 4539 mammal species. With Google Trends, I calculated whether Google searches for their common and scientific names have been increasing or decreasing over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…Urgent actions are thus required to prioritize the research effort and to raise public attention toward these overlooked TH species. Our results echo with a recent study that found an increase in Google searches for TH mammals only for large species ( 52 ), which are the most popular ( 53 ). We also found that some species that are actually categorized as DD by the IUCN show relatively high research effort, such as the John Dory ( Zeus faber ), the Giant grouper ( Epinephelus lanceolatus ), and the Yellowtail snapper ( Ocyurus chrysurus ).…”
Section: Discussionsupporting
confidence: 88%
“…Urgent actions are thus required to prioritize the research effort and to raise public attention toward these overlooked TH species. Our results echo with a recent study that found an increase in Google searches for TH mammals only for large species ( 52 ), which are the most popular ( 53 ). We also found that some species that are actually categorized as DD by the IUCN show relatively high research effort, such as the John Dory ( Zeus faber ), the Giant grouper ( Epinephelus lanceolatus ), and the Yellowtail snapper ( Ocyurus chrysurus ).…”
Section: Discussionsupporting
confidence: 88%
“…Google Trends, owned by Google Inc., is a publicly available tool that returns the relative frequency of any search term on the Google search engine (Choi & Varian, 2012), and it is being increasingly used for conservation culturomic research (Correia, Ladle, & Roll, 2021; Correia, Ladle, Jarić, et al., 2021). Because Google Trends is proprietary, numerous methodological considerations have been proposed to clarify the nature of the data returned and provide best practices on how to appropriately use this tool (Correia, 2019; Correia et al., 2019; Eichenauer et al., 2022; Ficetola, 2013; Nghiem et al., 2016; Steegmans, 2021; Van Huynh, 2023). Google Trends offers a “categories” search parameter to specify data for search terms with multiple meanings.…”
Section: Figurementioning
confidence: 99%